New minerals tsangpoite Ca5(PO4)2(SiO4) and matyhite Ca9(Ca0.5□0.5)Fe(PO4)7 from the D'Orbigny angrite. (29th June 2018) - Hwang, Shyh-Lung; Shen, Pouyan; Chu, Hao-Tsu; Yui, Tzen-Fu; Varela, Maria-Euginia; Iizuka, Yoshiyuki
Abstract: Tsangpoite, ideally Ca5 (PO4 )2 (SiO4 ), the hexagonal polymorph of silicocarnotite, and matyhite, ideally Ca9 (Ca0.5 □0.5 )Fe(PO4 )7, the Fe-analogue of Ca-merrillite, were identified from the D'Orbigny angrite meteorite by electron probe microanalysis, electron microscopy and micro-Raman spectroscopy. On the basis of electron diffraction, the symmetry of tsangpoite was shown to be hexagonal, P 63 / m or P 63, with a = 9.489(4) Å, c = 6.991(6) Å, V = 545.1(6) Å 3 and Z = 2 for 12 oxygen atoms per formula unit, and that of matyhite was shown to be trigonal, R 3 c, with a = 10.456 (7) Å, c = 37.408(34) Å, V = 3541.6 (4.8) Å 3 and Z = 6 for 28 oxygen atoms per formula unit. On the basis of their constant association with the grain-boundary assemblage: Fe sulfide + ulvöspinel + Al–Ti-bearing hedenbergite + fayalite–kirschsteinite intergrowth, the formation of tsangpoite and matyhite, along with kuratite (the Fe-analogue of rhönite), can be readily rationalised as crystallisation from residue magmas at the final stage of the D'Orbigny meteorite formation. Alternatively, the close petrographic relations between tsangpoite/matyhite and the resorbed Fe sulfide rimmed by fayalite + kirschsteinite symplectite, such as the nucleation of tsangpoite in association with magnetite ± other phases within Fe sulfide and the common outward growth of needle-like tsangpoite or plate-like matyhite from the fayalite–kirschsteinite symplectic rim of Fe sulfide into hedenbergite, infer that these new minerals and the grain-boundary assemblage might represent metasomatic products resulting from reactions between an intruding metasomatic agent and the porous olivine–plagioclase plate + fayalite-kirschsteinite overgrowth + augite + Fe sulfide aggregates. Still further thermochemical and kinetics evidence is required to clarify the exact formation mechanisms/conditions of the euhedral tsangpoite, matyhite and kuratite at the grain boundary of the D'Orbigny angrite.